Regulation of vascular endothelial function by red wine procyanidins: implications for cardiovascular health. Issue 20 (20th May 2015) - Khan, Noorafza Q.; Patel, Binta; Kang, Shahbaz S.; Dhariwal, Sukhjit K.; Husain, Farihah; Wood, Elizabeth G.; Pothecary, Mark R.; Corder, Roger
Abstract: The effects of oligomeric procyanidins (OPC) on vascular endothelial function provide a plausible explanation for the reduced incidence of coronary heart disease in red wine drinkers. Grape variety is an important influence on the amounts of OPC in wines. Red wines made from Aglianico, Sagrantino or Tannat grapes typically have higher OPC levels. The endothelial response to OPC induces atheroprotective changes in vascular function, which are likely mediated via oxidant signalling mechanisms originating from the mitochondrial electron transport chain. Graphical abstract: